Water Intake, Hydration Status, and Physiological Fluid Requirements among Universitas Tanjungpura Students during Equatorial Solar Culmination in Pontianak, Indonesia - Fadly, Dzul (Media Publikasi Cendekia Indonesia, 2025)
Water is an essential nutrient that plays a central role in maintaining physiological functions, including thermoregulation, nutrient transport, and metabolic balance. Pontianak, a city located precisely on the equatorial line, experiences a humid tropical climate with intense solar exposure. Although ambient temperatures during the study period remain within the city’s normal range, the solar equinox substantially increases direct solar radiation intensity, resulting in greater heat exposure and potential fluid loss. This study aimed to investigate the relationship between water intake and physiological fluid requirements among Universitas Tanjungpura students during the autumnal solar equinox (September 21-23). A cross-sectional design was applied involving 100 students aged 18–22 years selected through purposive sampling. Water intake was assessed using two consecutive 24-hour dietary recalls, and individual fluid requirements were estimated using the standard energy-based hydration formula (1 mL per kcal of total energy expenditure), with energy needs calculated using the Harris–Benedict equation. Pearson’s correlation test was used to analyze the association, with water intake treated as the independent variable. The results showed that mean water intake was 1,706 ± 485 ml/day, while mean physiological fluid requirements reached 1,954 ± 349 ml/day; 45% of participants met adequate hydration levels. A strong and significant positive correlation was observed between water intake and fluid requirements (r = 0.62; p < 0.001). Urine color assessment indicated that 40% of students exhibited signs of mild to moderate dehydration. These findings suggest that most students did not achieve optimal hydration, particularly under elevated environmental heat associated with solar culmination